Effectiveness of a brief lifestyle intervention targeting mental health staff: analysis of physical fitness and activity in the Keeping Our Staff in Mind study. Issue 1 (13th July 2020) - Fibbins, Hamish; Ward, Philip B; Curtis, Jackie; Watkins, Andrew; Lederman, Oscar; Morell, Rachel; Rosenbaum, Simon
Abstract : Background: People with mental illness die on average 15 years less than the general population, primarily to cardiometabolic disease. Lifestyle interventions are effective in reducing cardiometabolic risk but are not routinely provided to mental health consumers. Lifestyle interventions targeting mental health staff may be beneficial in changing culture surrounding physical health and subsequently improving consumer outcomes. This study examines exercise and fitness outcomes of a targeted lifestyle intervention directed at Australian mental health staff. Methods: A pragmatic single-arm intervention study was conducted within an Australian public mental health service. Mental health staff were provided a five-session individualised lifestyle intervention (incorporating exercise and nutritional counselling) over 5 weeks. Two waves of the programme were delivered between 2015 and 2016. This paper examines the exercise and fitness outcomes of the second wave of the study. Participants were assessed at baseline and at a 16-week follow-up. The primary exercise outcome was a measurement of cardiorespiratory fitness. Secondary outcomes included self-reported physical activity and a measurement of handgrip strength. Results: A total of 106 staff participated in this component of the study. Cardiorespiratory fitness increased significantly from baseline to follow-up (p<0.001). Significant improvements to physical activity occurred with decreases in sedentary time (p<0.0005) and increases in moderate-to-vigorous physical activity (p<0.005). Conclusion: Lifestyle interventions incorporating exercise counselling may improve the physical health of mental health staff. Such strategies may be effective in improving culture surrounding physical health and/or increasing the effectiveness of lifestyle interventions targeting mental health consumers.